Sphecid wasps of Slovenia (Hymenoptera: Ampulicidae, Sphecidae and Crabronidae) - Gogala, Andrej (Scopolia, 2011)
A list of sphecid wasps (Hymenoptera, Apoidea: Ampulicidae, Sphecidae and Crabronidae) known in Slovenia is compiled from the literature data, specimensin collections and own field work. 186 species are recorded: 3 species of Ampulicidae, 18 of Sphecidae and 165 of Crabronidae.
Keywords: Hymenoptera; ose grebače; Apoidea; favna; Ampulicidae; Slovenija; Sphecidae; Crabronidae; sphecid wasps; fauna; Slovenia